Glatiramer Acetate Treatment-Related Effects on Visual EPs and P300 Wave in Patients Suffering from Multiple Sclerosis - Major, Z.Z.; Văcăraş, V.; Buzoianu, A.D; Mureşanu, D.F. (Нейрофизиология, 2013)
Multiple sclerosis is an inflammatory neurological disease of young adults that leads to numerous therapeutic problems and to severe disability. Glatiramer acetate (GA) is a diseasemodifying drug used frequently for long-term treatment of the disease. We investigated the impact of GA treatment on the parameters of reversal-pattern visual evoked potentials and event-related P300 wave (reflecting visual acuity and cognitive dysfunction). Relapsingremitting multiple sclerosis patients either subjected to one-year-long continuous treatment with GA or without any disease-modifying therapy and also healthy controls were involved in the study. The above-mentioned parameters were analyzed at two time points, at the first recording and after one year. It was found that GA did not exert a significant influence on the phenomena studied at least during the one-year follow-up. This finding is in contrast to most of the clinical observations.